Effect of variety and nitrogen rate on the yield performance of boro rice - Chamely, SG; Islam, N; Hoshain, S; Rabbani, MG; Kader, MA; Salam, MA (Progressive Agriculture, 2015)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during the period from November 2010 to May 2011 to study the effect of variety and rate of nitrogen on the performance of Boro rice. The experiment comprised three varieties viz., BRRI dhan28 (V1), BRRI dhan29 (V2) and BRRI dhan45 (V3); and five rates of nitrogen viz., control (N0), 50 kg (N1), 100 kg (N2), 150 kg (N3)and 200 kg (N4) N ha-1. The experiment was laid out in a randomized complete block design with four replications. The growth analysis results indicate that the tallest plant (80.88 cm) and the highest number of total tillers hill-1 (13.80) were observed in BRRI dhan29 at 70 DATs and the highest total dry matter (66.41 g m-2) was observed in BRRI dhan45. The shortest plant (78.15 cm) and the lowest number of tillers hill-1 (12.41) were recorded from BRRI dhan45 and the lowest dry matter (61.24 g) was observed in BRRI dhan29. The tallest plants (84.01 cm), highest number of tillers hill-1 (14.06) and the highest dry matter (69.58 g m-2) were obtained from 200 kg N ha-1. The tallest plants (86.48 cm) and maximum dry matter (72.30 g m-2) were recorded from BRRI dhan28 with 200 kg N ha-1 and BRRI dhan45 with 200 kg N ha-1, respectively. The highest number of tillers hill-1 (15.14) was obtained from BRRI dhan29 with 50 kg N ha-1. The harvest data reveal that variety had significant effect on total tillers hill-1, effective tillers hill-1, non-effective tillers hill-1, panicle length, grain yield, straw yield and harvest index. The highest grain yield (4.84 t ha-1) was recorded from BRRI dhan29. The results of the experiment also indicate that total tillers hill-1, effective tillers hill-1, grains panicle-1, sterile spikelets panicle-1, grain yield, straw yield and harvest index were significantly affected by levels of nitrogen, while plant height, panicle length, 1000-grain weight were not significantly affected by levels of nitrogen. The highest grain yield (5.58 t ha-1) was obtained from 200 kg N ha-1. Interaction effect of variety × 200 kg N ha-1 produced the highest grain yield (5.82 t ha-1). From the results of the study it may be concluded that BRRI dhan29 rice may be cultivated with 200 kg N ha-1 for obtaining higher yield in AEZ 9 of Bangladesh. Progressive Agriculture 26:6-14, 2015